ความต้องการในการจัดการหลังความตายของคนเมืองในพื้นที่กรุงเทพมหานคร - อุษา เพียรทวีกิจ (จุฬาลงกรณ์มหาวิทยาลัย, 2024)
This research aims to study the postmortem management needs for Urbanites in Bangkok by using mixed method including quantitative research and qualitative research. Quota Sampling was used with total sample of 400 people; 200 Buddhists, 120 Muslims, 60 Christians, and 20 Nonreligious people. As for the qualitative research, semi-structured interview method was applied; 8 Buddhists, 6 Muslims, 3 Christians, and 3 Nonreligious people from Bangkok area population. The Chi-Square test is the tool that has been used to analyze the collected quantitative data and the qualitative data. The results of this study show that most people from the study sample desire the traditional form of burial or cremation as the first rank of the demand of the afterlife body (dead body) arrangement aspect; the next rank is an organ donation for medical uses. Based on the demand of funeral ceremony aspect, most people wish that every step of religious funeral ceremony would be held, whereas, some people wish to hold religious funeral ceremony but not all of the steps. Moreover, regarding to the trace and footprint management on digital platform, most people wish their accounts to be normally left after they leave this world, while some people prefer their accounts to be deactivated. Statistical Hypothesis Testing results indicate that the factors with the highest demand related to the demand on afterlife management of the urban living people in Bangkok area are the personal factors on occupations and education degrees. The next level factors are religious or belief factors and social factors of urban living on desire thought and expectation after leaving this world.